The Health Institutions in Iskenderun in the Second Half of the 19th Century and the Beginning of the 20th Century - Servet Özkan (Art-Sanat)
Since the establishment of the Ottoman Empire, Darüşşifas, which are the most important structures in the field of health, have been replaced by the modern hospitals by the 19th century. During this period, health institutions called by different names were built. The quarantines established in port cities against epidemic diseases have also attracted attention. Commercial activities and population increased with the drying of the marshes in Iskenderun, as one of the these cities, which began to develop in the 19th century. The buildings providing health services in the city are two quarantine buildings, a military hospital, a Gureba hospital and a French hospital. All of the structures are located close to the sea and at the point where they can be intervened during quarantine periods. Of these institutions, only the French-era hospital has survived to the present day. The existing sketches of the hospital, which were examined on-site and documented with photographs, have been redrawn digitally. In addition, the French inscription belonging to the identified structure was documented with photographs and translated. The Ottoman archives and Yıldız archives were searched for documents and images related to other structures, and the necessary documents were purchased. From the architectural point of view, it has been seen that the quarantines are wooden, small-scale and capable of responding to instant intervention. Data on the architecture of the military hospital, which is larger than the quarantines, has not been found. Gureba and French hospitals provided adequate health services for Iskenderun and reflected the artistic taste of the period with their Neoclassical styles. This study aims to examine the health institutions in Iskenderun in detail with archival data, historical images and on-site determinations, compare them with similar examples and introduce them to the scientific community.